Variations in Short Wave Radiation and Ocean Temperature in the Tropical Indian Ocean - Ahmad Fadlan; Muchammad Rizki; Tomi Ilham Pahlewi; Mohammad Ridwan Nur Prasetyo; Fajar Masan Bali; Imelda Umiyatul Badriyah; Muhammad Aldi Lukman (Buletin Oseanografi Marina, 2021)
The purpose of this study was to know the results of the relation between short wave radiation (SWR) and sea temperature. This study used data of SWR and sea temperature from RAMA buoy which part of the data was obtained by the INA-PRIMA 2019. Besides, the SWR and Sea Temperature model data from ERA-5 and Copernicus were required to see these spatial and temporal variations. Diurnal analysis to determine the sea temperature responds to SWR parameters. While monthly analysis to see the variations of SWR and the sea temperature during Indian Ocean Dipole (IOD). The results show that there is a different response at sea temperature for each layer to the SWR parameter in diurnal. SWR can affect sea temperatures until 20 meters of depth. There is a time lag between 2 and 3 hours when the sun heats the sea until the sea surface temperature increases. The 20 meters of depth has a lag time until 4 hours. As for 40 to 80 meters of depth, the sea temperature was not longer responded by SWR, and the temperature is changed by the strength of these mixing.Warm pools are generally located in East Indian Ocean and the high SWR were very strong in West Indian Ocean along an anual.